2021
DOI: 10.1093/noajnl/vdab119
|View full text |Cite
|
Sign up to set email alerts
|

Advances in the management of breast cancer brain metastases

Abstract: The development of breast cancer (BC) brain metastases (BrM) is a common complication of advanced disease, occurring in up to half of the patients with advanced disease depending on the subtype. The management of BCBrM requires complex multidisciplinary care including local therapy, surgical resection and/or radiotherapy, palliative care, and carefully selected systemic therapies. Significant progress has been made in the human epidermal growth factor receptor 2-positive (HER2+) BCBrM population due to novel b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 62 publications
0
13
0
Order By: Relevance
“…The significantly longer DBFFS in patients with HER2-positive CTC at any moment suggests that a focal approach with SRT for BCBM should be prioritized over WBRT to avoid the potential cognitive and quality of life impairments. In fact, there is a trend to consider SRT for patients with a better prognosis, or when active systemic therapy to the central nervous system is available [27][28][29]. The prospective observational study JLGK0901, involving 1194 patients with 1 to 10 newly diagnosed brain metastases treated exclusively with SRS, revealed that the median OS did not differ between the patients with 2 to 4 tumors and those with 5 to 19 (10.8 months in both groups), suggesting that SRT might be a suitable alternative for patients with up to 10 brain metastases [30].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The significantly longer DBFFS in patients with HER2-positive CTC at any moment suggests that a focal approach with SRT for BCBM should be prioritized over WBRT to avoid the potential cognitive and quality of life impairments. In fact, there is a trend to consider SRT for patients with a better prognosis, or when active systemic therapy to the central nervous system is available [27][28][29]. The prospective observational study JLGK0901, involving 1194 patients with 1 to 10 newly diagnosed brain metastases treated exclusively with SRS, revealed that the median OS did not differ between the patients with 2 to 4 tumors and those with 5 to 19 (10.8 months in both groups), suggesting that SRT might be a suitable alternative for patients with up to 10 brain metastases [30].…”
Section: Discussionmentioning
confidence: 99%
“…Between November 2016 and February 2018, 39 women were accrued. Patients underwent SRT with radiosurgery (SRS) or stereotactic fractionated radiotherapy (SFRT) in 68% (27) and 31% (12) of cases, respectively, with a median prescribed dose of 20 Gy (15)(16)(17)(18)(19)(20)(21)(22) with SRS and 27.5 Gy (25-30) in five fractions with SFRT.…”
Section: Baseline Characteristicsmentioning
confidence: 99%
“…In the curative intent setting, risk factors for developing brain metastases include HER2-positive or triple-negative subtype, young age, high grade, node positivity, and a diagnosis of inflammatory breast cancer. [26][27][28][29][30] Populationbased studies within the Surveillance, Epidemiology, and End Results database have reported that 11.5% of patients with de novo HER2-positive MBC 31 have brain metastases on initial presentation. Once a patient develops metastatic disease, the risk of brain metastases accumulates over time, reaching up to 50% cumulative incidence in patients with HER2-positive breast cancer.…”
Section: Prevention and Treatment Of Brain Metastases Incidence And E...mentioning
confidence: 99%
“…As many as 30% of patients with advanced, metastatic HER2+ breast cancer will develop BrM ( 6 ). Current standard of care options for HER2+ BCBrM include radiation therapy (stereotactic radiosurgery [SRS] or whole brain radiation therapy [WBRT]), brain permeable systemic therapies, and/or neurosurgical resection when appropriate ( 7 ). A multimodal approach combining these different treatment modalities has improved the overall survival and functional outcomes of patients with BCBrM.…”
Section: Introductionmentioning
confidence: 99%